Analisis Kemampuan Berpikir Kritis Matematis: Dampak Model Pembelajaran Problem Based Instruction - Suhita, Suhita (Universitas Islam Negeri Raden Intan Lampung, 2019)
This study aims to improve students' critical thinking skills through the application of Problem Based Instruction learning models. This research is a quasi experiment. The research subjects in this study were students of class VIIIA SMP Negeri 24 Bandar Lampung Academic Year 2017/2018 with a total of 32 students with a cluster random sampling technique. The required data is obtained through observation, documentation and tests using description questions. The collected data was analyzed by quantitative analysis techniques. The instruments used to collect data are tests of critical thinking skills. Data from the test results and observation sheets were analyzed quantitatively. The results showed that students 'critical thinking skills in the control class were 14.23% and included in the low category, while in the experimental class students' critical thinking abilities reached 87.5% or included in the high category. So, it can be said that the Problem Based Instruction learning model can improve students 'critical thinking skills, where students' critical thinking abilities increase from each cycle. So that the Problem Based Instruction learning model can be applied in learning both in mathematics and in other lessons.